Does Transition to IFRS 16 Affect Companies Financial Performance: The Case of Baltic Listed Companies - Legenzova Renata; Žilaitytė Liveta (Organizacijų Vadyba: Sisteminiai Tyrimai, 2023)
The paper assesses the effect of transitioning to IFRS 16 on Baltic listed companies’ financial performance. The results revealed that 74.63% of sample companies were affected with an average 8.68% increase in total assets and 13.03% increase in total liabilities. Return on assets and assets turnover ratios of the affected companies decreased by an average of 8.33%, the quick ratio and current ratio decreased by 7.84%, while the debt-to-equity ratio increased by 28.63%. The sectors most heavily impacted by transitioning to IFRS 16 were communication services and basic materials sectors.